21st century relining – the path to greater mine site profitability - P Rubie; J Russell (The Australasian Institute of Mining and Metallurgy, 2018)
This paper looks at the past, present and not too distant future of grinding mill relining.Since the adoption of autogenous grinding (AG) mills and semi-autogenous grinding (SAG) mills as the primary ore reducing devices in the comminution circuit, plant shutdown frequency and duration has largely been driven by the liner maintenance requirements of these mills.The past 30 years have seen the introduction of many technologies to reduce relining times and frequencies. Advanced relining systems have been developed which include single and twin Mill Relining Machines, capable of placing large (up to 8000 kg) liners, high energy recoilless THUNDERBOLT Hammers, and high capacity Feed Chute Transporters. Despite these advances, today many of the hazards associated with mill relining remain and reline times still vary considerably between mine sites. A sophisticated discrete event simulation program, designed to analyse the mill relining process, has revealed the dominant influences on reline times of crew performance and of the need for safe access to larger segments of the mill.A new generation of advanced and semi-automated technologies is currently being tested that will address these remaining challenges. These technologies remove people from the hazardous environment inside the mill and will allow techniques used in modern advanced manufacturing to provide a near-future step change in mill relining safety and performance.CITATION:Rubie, P and Russell, J, 2018. 21st century relining – the path to greater mine site profitability, in Proceedings 14th AusIMM Mill Operators' Conference 2018, pp 621–640 (The Australasian Institute of Mining and Metallurgy: Melbourne).